Preparation and study on the properties of acrylonitrile butadiene styrene/polyphenylene oxide polymer blend. Issue 2 (24th April 2021) - Trung, Tran Huu; Huynh, Mai Duc; Cong, Do Van; Thai, Nguyen Thi; Tham, Do Quang; Nguyen,; Dat, Huu; Dung, Trinh Quang; Hai, Luong Như; Giang, Nguyen Vu
Abstract: Blends of polyphenylene oxide (PPO) and acrylonitrile butadiene styrene (ABS) were prepared by melt‐mixing method. Flammability of these blends was studied by using UL‐94 (plastics flammability standard) and LOI (limited oxygen index) tests. The results showed the role of PPO as flame retardant in the blends which can inhibit the burning process. All blends of PPO and ABS were graded as V‐1 and LOI values were higher than 21. As a physical mixture, tensile strength of PPO/ABS blends maintained values between the tensile of neat ABS and PPO. Melting rheology characterization of samples showed that the fabrication of PPO/ABS blend consumed less energy than that of PPO polymer. Differential scanning calorimetry analysis investigated that PPO and ABS were partially miscible in blend with two glass transition temperatures (Tg) which ranged between Tg of ABS and PPO.